UHPLC-Q-TOF/MS unveils metabolic diversity in Paris L. and highlights medicinal potential of five newly identified species - Sun, Kangmeng; Shao, Yingying; Li, Rong; Wang, Zhi; Wang, Jinghan; Luan, Xinyu; Wu, Changqiao; Wang, Liya; He, Chunnian; Tang, Qi (Frontiers in Pharmacology, 2025)
Paris species are widely distributed across China, with their rhizomes traditionally used in Chinese medicine. P. polyphylla var. chinensis (PPC) and P. polyphylla var. yunnanensis (PPY) are listed in the official pharmacopeia and have been extensively studied, however, the metabolic diversity of other species within the genus remains largely unexplored. To address this gap, a comprehensive UHPLC-Q-TOF/MS-based metabolomic analysis was conducted on rhizomes from 26 Paris species and varieties, five of which have been published in recent years. Multivariate statistical analyses, including PCA and HCA, revealed three distinct metabolic groups. Group 1, dominated by pennogenin saponins, exhibited the highest overall steroidal saponin content. Group 2 displayed lower total saponin levels and marked metabolic heterogeneity, whereas Group 3 was characterized by a predominance of diosgenin saponins. Comparative analysis of the five newly identified species and the two pharmacopoeial species identified 24 common metabolites and 43 differentially accumulated metabolites. Notably, P. xuefengshanensis and P. qiliangiana contained relatively high levels of Polyphyllin I, II, and VII, with P. xuefengshanensis surpassing PPY and PPC. Additionally, P. tengchongensis exhibited notably high relative levels of Gracillin and Protogracillin. These findings highlight the presence of unique metabolites and relatively high concentrations of bioactive steroidal saponins in the newly identified species, suggesting their potential medicinal value, particularly for antitumor and hemostatic applications. This study provides new insights into the metabolic diversity of Paris species and supports the exploration of these under-researched resources for pharmacological use.